2009
DOI: 10.1007/s00381-009-1050-0
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus warneri ventriculoperitoneal shunt infection: failure of diagnosis by ventricular CSF sampling

Abstract: S. warneri constitutes an emergent contaminant of catheters and prostheses. We found only a detailed report of S. warneri infection of a ventriculoatrial shunt. If manifestations of peritoneal involvement in shunted patients would occur, the attention should be shifted to the distal component of the shunt hardware, even in the presence of a normal ventricular CSF as happened in our case to avoid unnecessary delay in diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Divergences in composition of CSF from these compartments have also been attributed to the diverse location of the infecting focus 6 . Similar differences in ventricular and spinal fluid have been reported in cases of neurocysticercosis, tuberculous and pneumococcal meningitis, and in children with leptomeningeal spread of CNS tumors 4,6,9,14 . Interestingly, Heringer et al have reported one case with negative ventricular and lumbar CSF cultures, in which only the cisternal CSF yielded acid-fast bacilli 6 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Divergences in composition of CSF from these compartments have also been attributed to the diverse location of the infecting focus 6 . Similar differences in ventricular and spinal fluid have been reported in cases of neurocysticercosis, tuberculous and pneumococcal meningitis, and in children with leptomeningeal spread of CNS tumors 4,6,9,14 . Interestingly, Heringer et al have reported one case with negative ventricular and lumbar CSF cultures, in which only the cisternal CSF yielded acid-fast bacilli 6 .…”
Section: Discussionsupporting
confidence: 77%
“…In addition, an LP should not be performed in patients who present with impaired consciousness as cerebral herniation may occur even when neuroimaging has been normal 2 . On the other hand, in patients given a ventriculoperitoneal shunt, CSF analysis is routinely performed via the valve reservoir, given that the analysis of shunt fluid is generally regarded as the most reliable method for the diagnosis of a valve infection 9,11 . In our patients, initial CSF sampling was performed directly from the ventricles at the time of VP shunt insertion, via the valve reservoir or from the external ventricular drain respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The second most frequently identified species, S. warneri was isolated from one of the healthcare units and four hospital wards, including cardiology, sickroom of an intensive care unit and an infectious ward, whose patients' immune system may be compromised. This information might be important, as this species was reported to cause infections in hospitalized patients and was also suggested as a cause of, among others, ventricular shunt infections, endocarditis and even sepsis (32,33). One of the most dangerous CoNS, S. haemolyticus was isolated from 4 sites (n = 5) -three hospitals, including the isolation ward of an ICU.…”
Section: Discussionmentioning
confidence: 99%
“…
Purpose The aim of the article is to describe an immunological reaction to shunt infection in children with hydrocephalus. The main cause of shunt infection involves methicillin resistant Staphylococcus epidermidis (Bhatia et al Indian J Med Microbiol 35:120–123, 2017 ; Hayhurst et al Childs Nerv Syst 24:557–562, 2008 ; Martínez-Lage et al Childs Nerv Syst 26: 1795–1798, 2010 ; Simon et al PLoS One, 2014 ; Snowden et al PLoS One 8:e84089, 2013 ; Turgut et al Pediatr Neurosurg 41:131–136, 2005 ), a bacterial strain which is responsible for the formation of biofilm on contaminated catheters (Snowden et al PLoS One 8:e84089, 2013 ; Stevens et al Br J of Neurosurg 26: 792–797, 2012 ).
Methods The study group involved 30 children with congenital hydrocephalus after shunt system implantation, whose procedures were complicated by S .
…”
mentioning
confidence: 99%